THE EFFECTIVENESS OF REALISTIC MATHEMATICS EDUCATION LEARNING APPROACH ON CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Susanti, Pudji (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
Critical thinking is an ability that students must have to make a reasonable decision based on facts in solving a problem correctly. But in reality not all students have this ability. This study aims to determine the effectiveness of applying the Realistic Mathematics Education approach compared to the direct learning model on the critical thinking skills of elementary school students. This study uses a quasi-experimental method. The research design was a non-equivalent control group design. The sample of this research is the fourth grade students of SDN 2 Mangunrejo as the experimental class and the fourth grade students of SDN 3 Mangunrejo as the control class. The instrument used to measure critical thinking skills is a written test. The average value of student learning outcomes for the experimental class is 82.30, while the control class is 62.33. Thus it can be concluded that there is a difference in the average student learning outcomes between the RME class and the control class. The results of the Independent Sample t-test showed a sig (2-tailed) value of 0.00 0.05 so it can be concluded that there is a significant difference between the average student learning outcomes in the RME class and the control class. From the results of data analysis, it can be concluded that the Realistic Mathematics Education approach is more effective in improving critical thinking skills when compared to the direct learning model.